Production Integration in the European Union - Hakan Nordström; Harry Flam (Center for Economic Studies and ifo Institute (CESifo), 2018)
Measured by trade in intermediate inputs, economic integration has increased between 2000 and 2014 between members of the European Union and even more with non-members. Integration is negatively related to economic size and positively to the number of years as a member. Germany is the largest hub in the production network and the centre of gravity has moved eastward. Older member states are increasingly exporting service inputs and new member states primary and manufacturing inputs. Wages are increasing faster in countries with low initial wages, indicating wage convergence as a result of production integration.
Keywords: E10; F10; F60; J31; 330; global value chains; economic integration; input-output models; wage convergence